Bis‐Sulfonyl O, C, O‐Chelated Metallylenes (Ge, Sn) as Adjustable Ligands for Iron and Tungsten Complexes. Issue 4 (18th December 2015) - Deak, Noémi; Petrar, Petronela M.; Mallet‐Ladeira, Sonia; Silaghi‐Dumitrescu, Luminiţa; Nemeş, Gabriela; Madec, David
Abstract: The synthesis and characterization of an E2 CE2 bis‐sulfonyl aryl pincer ligand and its efficiency for the stabilization of compounds containing low‐valent Group 14 elements (Ge and Sn) are reported. Complexation reaction of these metallylenes with iron or tungsten complexes resulted in the modulation of the oxygen atoms of the sulfonyl groups implicated in the stabilization of the Group 14 elements, demonstrating the original adjustable character of the bis‐sulfonyl O2 S‐C‐SO2 aryl pincer. Abstract : New pincer ligand ! Intramolecularly S=O‐stabilized heteroleptic germanium(II) and tin(II) compounds have been characterized and used as adjustable ligands in transition‐metal complexes (see scheme).